Quantification of localised vascular wedge‐shaped defects in glaucoma. (26th July 2022) - Saks, Danit; Schulz, Angela; Sheriff, Samran; Shen, Ting; Gupta, Vivek; Qassim, Ayub; Ridge, Bronwyn; Pham, Ryan; Craig, Jamie; Graham, Stuart; ,
Abstract: Background: Vascular dysfunction plays a considerable role in glaucoma pathogenesis. Previous glaucoma case studies described localised wedge‐shaped vascular defects, similar to retinal nerve fibre layer (RNFL) wedge defects. This study investigates the prevalence and quantification of this vessel loss, in relation to primary open angle glaucoma (POAG) parameters. Methods: This study included 608 eyes (351 participants): 192 PROGRESSA study participants (342 eyes) with suspect, preperimetric or early manifest POAG, observed for vascular wedge defect presence (cohort one); an additional 114 individuals (cohort two—208 eyes) with POAG at various stages of progression for wedge characterisation; and 38 controls (56 eyes). Vascular wedge defects were observed using optical coherence tomography angiography (OCTA). Wedge parameters and vessel densities were quantified using ImageJ software. RNFL and ganglion cell layer inner plexiform layer (GCLIPL) from OCT scans, and mean deviation (Humphrey visual field 24–2) were also assessed. Results: Vascular wedge defects were found in 45/342 eyes (13.2%) in cohort one, in 41/208 eyes (19.7%) in cohort two and were not found in controls. Wedge defects were mostly inferotemporal (80%), and present at all disease stages. They were associated with visual field loss in the opposite hemisphere, thinner RNFL ( p  < 0.001), thinner GCLIPL ( p  = 0.003), and focal RNFL loss corresponding with the vascular defect region. Conclusion: Vascular wedge defects are present at all POAG stages even before functional change and are strongly concordant with focal RNFL loss. Further research is needed to explore these defects in particular their temporal relationship with clinical measures of POAG.